A fájdalmas és az ellenálló anya: „Zsidó” identitáskép a Nincstelenekben - Szűcs, Teri (Studia Litteraria, 2016)
The mother is a central figure in the works of Szilárd Borbély, and she usually appears as Mater Dolorosa, the sorrowful mother. The novel Nincstelenek is exceptional in this respect, because it also presents her as the resisting mother. The novel focuses on the aggressive attribution of identities, the exclusion of those who are considered Jewish – and thus: as the Other – from the community. This process stretches over several generations. The only character in the novel whose attitude towards this violent attribution of inferior identity consciously changes is the mother. While her husband and her children are stigmatized by blood lineage, in the case of the mother Jewishness is a choice. Thus she becomes able to understand the events that befall her family, their exclusion, their poverty. She offers this insight to her husband at the end of the novel, and he finally accepts the status of the Jew, and participates in the Shabbat ritual. The peculiar practice of the mother is an attempt to grasp agency.